THE FRACTURED RELATIONSHIP BETWEEN FATHER AND SON AS REVEALED IN INDU SUNDERASAN’S TAJ TRILOGY (International Journal of Food and Nutritional Sciences, 2022)
Disintegration of families and the fading of filial love is a common phenomenon in the postmodern life. The relationship between the father and the son has been a problematic and complicated intriguing. The generation gap between them creates a lot of strife andmisunderstanding. Even in the Mughal Empire, the father and son often clash against each other, mostly for securing power and crown. In Indu Sundaresan‟s TheTwentieth Wife, this crisis is examined very closely. Moreover, the children, denied parental love and attention are misled by rebels who use them for their own selfish profits. Often these royal children are used as tools by the enemies to rebel against the father figure. Thus a wide gap is formed between the father and the son. But the royal women especially the daughters are denied political power. But, such struggles for power do not enter into the woman‟s Zenana. They remain faithful wives, daughters and sisters. This is exemplified through the novel TheTwentieth Wife.